CPC-040 Design and Assessment of an E-Learning Course to Train Clinical Pharmacists in Vitamin K Antagonist (VKA) Consultations. (12th March 2013) - Barbier, E; Launay-Vacher, G; Chaumais, MC; Rieutord, A; Haddad, R; Courtin, C
Abstract : Background: Since 2009, clinical pharmacists have been performing about 150 vitamin K antagonist (VKA) consultations annually in all wards of our hospital. This 24-hour service requires the training of about 15 to 20 pharmacists per year. A very comprehensive but time-consuming training course had been set up. Purpose: To design and implement an E-learning course to train clinical pharmacists for VKA consultations. Materials and Methods: A database of 70 questions (Qs) (35 Level 1 Qs for beginners paired to 35 Level 2 Qs for advanced learners). Each set was divided into 5 themes (biology, side effects, drug interactions, hospital practise and medicines). The training involves six steps (from S1 to S6) An assessment of knowledge before training (S1, 10 quizzes level 1) Theoretical training using a slideshow (S2) 4 role-plays involving a patient and a pharmacist (S3) A reassessment of knowledge (S4, 10 quizzes level 2) A practical evaluation of running a VKA consultation at the bedside is performed by the pharmacy resident (S5). The score required to complete this step is ≥8 out of 9. A satisfaction questionnaire (S6) The validation method was performed with 10 pre-registration pharmacy students (PRPs). E learning was developed according to SCORM standards. Results: The individual progression of PRPs was significant (increase of 2.1 points/20, significant p < 0.025). A high level of satisfaction and autonomy was expressed when training was completed. The shift towards e-learning for steps S1 to S4 was much appreciated, particularly distance learning, free access to slideshow, learning flexibility, flash animation for role play. Performances observed for trained consultants at the bedside during S5 were very similar to those obtained prior to E-learning. Conclusions: Anticoagulant monitoring and related patient education is a major issue. Training consultant pharmacists is particularly critical. We demonstrated that E-learning can save much time while providing efficient, customised training to healthcare professionals. Our course will be soon extended to two teaching hospitals belonging to the same group. In 2013, details of new oral anticoagulants will be added to the course. No conflict of interest.